Hubungan Faktor Predisposisi Pekerja dan Kepatuhan Penggunaan APD terhadap Unsafe Action pada Pekerja Bagian RAM di PT. XYZ Jambi - Astrid Mei Heza; Ismi Nurwaqiah Ibnu; Ashar Nuzulul Putra (Lembaga Pengembangan Kinerja Dosen, 2025)
Until April 2024, there were 17 reported cases of unsafe actions within the company. This quantitative, cross-sectional study aimed to examine the relationship between predisposing factors and compliance with personal protective equipment (PPE) use and unsafe actions among RAM workers at PT XYZ Jambi. The study involved 78 out of 125 workers, selected through purposive sampling from November 2024 to March 2025. Data were collected using validated questionnaires assessing unsafe actions, knowledge, attitudes, motivation and PPE compliance, and analyzed using the chi-square test in SPSS version 25. Results showed that 53,8% of workers exhibited a high level of unsafe action. Education level, attitude, and PPE compliance were significantly associated with unsafe actions, while age, knowledge, and motivation were not. In conclusion, education, attitude, and PPE compliance are key factors related to unsafe actions among RAM workers. It is recommended that workers enhance their awereness and motivation to avoid unsafe actions.